2022
DOI: 10.3390/genes13061063
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Association of Hepatocyte Nuclear Factor-1α with Glycosylation in Post-Traumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) is a complex trauma-related disorder, the etiology and underlying molecular mechanisms of which are still unclear and probably involve different (epi)genetic and environmental factors. Protein N-glycosylation is a common post-translational modification that has been associated with several pathophysiological states, including inflammation and PTSD. Hepatocyte nuclear factor-1α (HNF1A) is a transcriptional regulator of many genes involved in the inflammatory processes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Although genetic influence on these processes is considered negligible, low heritability N-glycans are often influenced by epigenetic factors, such as changes in DNA methylation [ 62 ]. In particular, recent studies have shown a significant correlation between the methylation of the HNF1A gene and the abundance of the highly sialylated tri- and tetra-antennary N-glycans including the A4G4S4 glycan [ 37 , 38 ]. Since the rs6573604 polymorphism is located within the microRNA 4708 gene ( MIR4708 ), in close proximity of the 5′ end of the FUT8 gene, it is possible that it affects the plasma levels of these N-glycans through molecular epigenetic mechanisms [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genetic influence on these processes is considered negligible, low heritability N-glycans are often influenced by epigenetic factors, such as changes in DNA methylation [ 62 ]. In particular, recent studies have shown a significant correlation between the methylation of the HNF1A gene and the abundance of the highly sialylated tri- and tetra-antennary N-glycans including the A4G4S4 glycan [ 37 , 38 ]. Since the rs6573604 polymorphism is located within the microRNA 4708 gene ( MIR4708 ), in close proximity of the 5′ end of the FUT8 gene, it is possible that it affects the plasma levels of these N-glycans through molecular epigenetic mechanisms [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…HNF1A is considered a major molecular regulator of fucosylation, possibly by regulating the expression of FUT8 and antennary fucosyltransferases (FUT3, FUT5, FUT6). The genetic and epigenetic associations of the HNF1A gene with levels of several highly branched and sialylated plasma N-glycans, as well as with the core- and antennary-fucosylated IgG N-glycans, were reported in recent studies [ 37 , 38 ]. Numerous single nucleotide polymorphisms (SNPs) were suggested to significantly affect the IgG and plasma N-glycan composition, among which the most prominent ones were located within or near the FUT8 locus and associated with the A2 and A2BG2 glycan levels, as well as with the core-fucosylated FA2G2 and FA3B1G1 N-glycans [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%